THE POWER OF TECHNOLOGY IN ENHANCING RUSSIAN LANGUAGE EDUCATION - Parpieva Makhsudakhon Makhmudjonovna (Journals Park Publishing, 2023)
This article covers the fact that the study of Russian language education has always been an urgent topic, especially since communication across cultures has become increasingly important. If we want to improve our skills in the Russian language we must forget outdated textbooks and explore the world of online resources, videos, series and interactive events. We can speak Russian in a short time like a professional.
Keywords: Globalization, language, Information Technology, Russian TV shows, online resources, stimulating learning environment, interactive and immersive learning, online forums.